Overexpression of MTHFD2 represents an inflamed tumor microenvironment and precisely predicts the molecular subtype and immunotherapy response of bladder cancer - Shi, Xiaokai; Peng, Xiangrong; Chen, Yin; Shi, Zebin; Yue, Chuang; Zuo, Li; Zhang, Lifeng; Gao, Shenglin (Frontiers in Immunology, 2023)
Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2), whose aberrant expression is common in cancers, has recently been identified as a potential regulator of immune response. However, its immune-related role in bladder cancer (BLCA) and its association with immunotherapy efficacy remain unclear. Here, in this study, MTHFD2 was found to be positively associated with several immunological features of inflamed tumor microenvironment (TME) in various cancers and could predict BLCA patients' prognosis. In BLCA, high expression of MTHFD2 was observed to be positively related with cancer-immunity cycle, infiltration of several immune cells, expression of immunoregulators and T cell inflamed scores, indicating a positive correlation with inflamed TME. Besides, patients with high MTHFD2 expression were more likely to be basal-like subtypes and respond to BLCA treatments, including immunotherapy, chemotherapy and target therapy. The clinical data of IMvigor210 cohort confirmed the higher response rates and better survival benefits of immunotherapy in high MTHFD2 expression patients. Collectively, high MTHFD2 predicts an inflamed TME, basal-like subtype and better response to various therapeutic strategies, especially the ICB therapy, in bladder cancer.